Introduction to finite fields and their applications - Lidl, Rudolf 1948-; Niederreiter, Harald 1944- (Cambridge Univ. Press, 1994)
The first part of this book presents an introduction to this theory, emphasising those aspects that are relevant for application. The second part is devoted to a discussion of the most important applications of finite fields, especially to information theory, algebraic coding theory and cryptology. There is also a chapter on applications within mathematics such as finite geometries, combinatorics and pseudo-random sequences